Telling the Other's side: Formulating others' mental states in driver training. (March 2019) - Broth, Mathias; Cromdal, Jakob; Levin, Lena
Abstract: This article examines ascriptions of mental states to other road users in live traffic driver training. Through this practice, instructors formulate how others make sense of the trainee driver's car. Using multimodal conversation analysis, we demonstrate how others' side formulations support trainee drivers' communicative handling of the car during ongoing coordination events. In contrast, formulations occurring after coordination events serve educational ends, yielding the generic inferential practices by which competent drivers make contextual sense of others' actions. Therefore, others' side formulations comprise an important instructional resource for introducing neophyte drivers into the real-world theorizing, rendering traffic its orderly social character. Highlights: Instructors treat other drivers' behaviour as displaying their reasoning. Learning to read other drivers' intentions is part of driver training in live traffic. Instructors make claims about others drivers' thinking to account for instructions. Others' side tellings support trainee drivers' coordination with other vehicles. Others' side tellings after a coordination event reconstruct it pedagogically.